PHARMACOLOGICAL STUDIES OF THE EXPERIMENTAL PREPARATION IMKAR-120 - Levytska, V. A.; Berezovsky, A. V. (Scientific Progress & Innovations, 2019)
At present, preparations based on imidocarb (Imidosan, Pyrosan, Pyrostop, Forticarb, etc.), which are more effective and convenient to use than others, are widely used in the treatment of dogs for babesiosis. The Ukrainian analogue of the above-mentioned antiprotozoan veterinary preparations is Imkar-120, with the active substance of imidocarb dipropionate, has recently been introduced in the market, It provides a wide range of antiprotozoan effects on the causal agents of pyroplasmoses of Babesia, Theileria, Nuttallia and Anaplasma genera with their mono- or mixed infestations. The studies of pharmaco-kinetics of imidocarb was conducted in 2018 on the basis of the Veterinary clinic "Fauna-Service" in the town of Kamianets- Podilskyi on 5 non-pedigree dogs, weighing from 14 to17 kg. Before beginning the experiment, the animals were clinically examined; their biochemical and general blood tests were made. According to the results of the examination, no pathologies were detected. Imkar-120 was administered to animals once, intramuscularly at the dose of 4.5 mg/kg. During and after the preparation administration no one of the dogs, had pain reaction, swelling of the injection site or any other side effects. While studying the general condition of the animals we observed a slight increase in clinical indices. So, after administering the preparation, the average heart rate was 138 beats per minute, the number of respiratory movements per minute was 27, and the rectal temperature was 38.5 0C. The peak concentration of Imkar-120 in the animal blood was observed one hour after the injection, and averaged 3.60 μg/ml. Starting from 15 minutes after administering, the concentration in the blood already averaged 0.76 μg/ml and during an hour it increased, reaching the maximum of 3.98 μg/ml in one dog. After that the period of elimination began. In 12 hours, the level of the active substance in the blood was greatly reduced and within 24 hours after the injection it was detected in very low concentrations, on the average 0.30 μg/ml. On the 7th day after administering the preparation it was not detected in the blood. The absorption of Imkar-120 after its intramuscular administration at the dose of 4.5 mg/kg was quite rapid. After administering the preparation no side reactions were observed, therefore, Imkar- 120 is recommended for using at the treatment of babesiosis and other blood-parasitic diseases of dogs.